Poor numbers : how we are misled by African development statistics and what to do about it - Jerven, Morten (Ithaca, London: Cornell University press, 2013)
Poor Numbersis the first analysis of the production and use of African economic development statistics. Morten Jerven's research shows how the statistical capacities of sub-Saharan African economies have fallen into disarray. The numbers substantially misstate the actual state of affairs. As a result, scarce resources are misapplied. Development policy does not deliver the benefits expected. Policymakers' attempts to improve the lot of the citizenry are frustrated. Donors have no accurate sense of the impact of the aid they supply.
Includes bibliographical references (pages 163-177) and index.
oif 09/09/14
Loan
Keywords: Economic development; National income; Economic indicators; Economic conditions - Statistics; Africa, Sub-Saharan